PELATIHAN JURU BUKU KSP/USP KOPERASI BERBASIS KOMPETENSI SKKNI KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Setyanto, Eddy; Hidayat, R Taufik; Andini, Lembah Dewi (DEVOSI, 2024)
Cooperatives as economic entities based on the principles of togetherness and shared prosperity require the existence of bookkeepers who are skilled and knowledgeable in managing finances and administration. Training for KSP/USP Cooperative Bookkeepers Based on Competency in Districts/Cities in South Sumatra Province has had a positive impact on the competency, skills and knowledge of Savings and Loans Cooperative/Usp bookkeepers. The training methods used include a practical approach with a focus on direct application in the cooperative context. The training participants consisted of cooperative bookkeepers from various cooperatives in different regions in South Sumatra province. Training focuses on basic understanding of organizational management, cooperative accounting, cash flow management, accurate financial reporting, and the application of technology in administration. The training results showed a significant increase in the bookkeeper's technical skills and conceptual knowledge after attending the training. Participants also reported increased confidence in managing their day-to-day administrative tasks. Apart from that, this training also encourages collaboration between cooperatives and the exchange of best practices in financial management. The final result is that participants are provided with a certificate from BNSP. In conclusion, competency-based training has proven effective in improving the skills and knowledge of cooperative bookkeepers. This has important implications in increasing the operational efficiency of cooperatives as well as increasing members' and stakeholders' trust in cooperative financial management